2016
DOI: 10.1128/aac.02285-15
|View full text |Cite
|
Sign up to set email alerts
|

Incompatible Natures of the HIV-1 Envelope in Resistance to the CCR5 Antagonist Cenicriviroc and to Neutralizing Antibodies

Abstract: bCenicriviroc is a CCR5 antagonist which prevents human immunodeficiency virus type 1 (HIV-1) from cellular entry. The CCR5-binding regions of the HIV-1 envelope glycoprotein are important targets for neutralizing antibodies (NAbs), and mutations conferring cenicriviroc resistance may therefore affect sensitivity to NAbs. Here, we used the in vitro induction of HIV-1 variants resistant to cenicriviroc or NAbs to examine the relationship between resistance to cenicriviroc and resistance to NAbs. The cenicriviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Holman and Gabuzda also reported the involvement of Pos315 in HAND-predicting signature [ 21 ]. Pos315 resides in the tip of the V3-loop, and various variants such as R315K, R315T, and R315Q have been associated with reduced efficacy of neutralizing antibodies (NAbs) [ 35 38 ]. In our analysis, R315K and R315Q were enriched in the HAND and NonHAND cases, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Holman and Gabuzda also reported the involvement of Pos315 in HAND-predicting signature [ 21 ]. Pos315 resides in the tip of the V3-loop, and various variants such as R315K, R315T, and R315Q have been associated with reduced efficacy of neutralizing antibodies (NAbs) [ 35 38 ]. In our analysis, R315K and R315Q were enriched in the HAND and NonHAND cases, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9 No. 3 fusion inhibitors drug [20,36] (Table 1), but appear to escape from neutralizing antibodies [20,[36][37][38][39]. Although additional mutations can promote drug resistance or escape from the immune system, the potential fitness cost of the variants may affect the pathogenesis of HIV-1.…”
Section: Resultsmentioning
confidence: 99%
“…These sequences encompass the ten most frequent V3 motifs around the world, together with GPGR and GPGQ. The binding capacity of anti-V3 neutralizing antibodies can be reduced in the presence of GPGK, GAGR, GLGR, and GPGA [20,36,40,[45][46][47], impairing the course of HIV-1 infection and affecting a vaccine design (Table 1). Contrarily, GWGR increases the neutralizing capacity of antibodies [48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the MVC-resistance mutations might improve the accessibility of epitopes for the NAbs and, therefore, be incompatible with resistance to the NAbs ( Yoshimura et al, 2014 ). More recently, Kuwata et al (2015) showed that resistant variants against a CCR5 inhibitor, cenicriviroc, also became sensitive to three NAbs: VRC01 (CD4bs), 4E9C, and 0.5γ (V3).…”
Section: Effect Of Mvc-resistance Mutations On Sensitivity To Nabsmentioning
confidence: 99%